American Indian materials, Anthony F. C. Wallace Papers - Wallace, Anthony F. C., 1923-2015; Kane, Michal Lowenfels; Smith, Mina Brayley; Akweks, Aren; Ka-Hon-Hes; Gansworth, Nellie; Cornplanter, Jesse J.; Wallace, Paul A. W.; Speck, Frank G. (Frank Gouldsmith), 1881-1950; Spotted Elk, Molly, 1903-1977 (1937)
The Anthony F. C. Wallace Papers are a vast collection of materials relating to Wallace's work at the intersection of anthropology, psychology, and history. This entry is intended as both a general introduction and a catch-all for Native and Indigenous materials not indicated in another entry. Researchers are advised to see also the other entries devoted to specific cultural groups, and view the finding aid for a detailed discussion of Wallace's long and varied career and an itemized list of the collection's contents to truly get a sense of the depth and breadth of the A. F. C. Wallace Papers. Of particular interest will be Series II. Research Notes and Drafts, particularly Subseries A. Indian Research, which contains correspondence, notes and drafts from Wallace's research among the Seneca and Tuscarora. Some overlapping Native American material is in Subseries B. Revitalization and Culture. Also of particular interest will be Series IX. Indian Claims, which contains Wallace's work (with his research assistant Michal Lowenfels Kane) as an expert witness for several Native American land claims, including those of Creek, Dakota (Sioux), Delaware, Haudenosaunee (Iroquois), Iowa, Kickapoo, Meskwaki (Fox, Sac and Fox, or Sauk and Fox), Miami, Muckleshoot, Oto-Missouri, Pawnee, Shawnee, and Wyandot peoples. Another concentration of materials can be found in Series VII. Eastern Pennsylvania Psychiatric Institute and pertain to Wallace's study of "arctic hysteria" (piblokto) among Greenland Inuit. Subseries B. U.S.-Soviet Commission on Anthropology of Series VI. Consulting and Committee Work also contains items on arctic populations. Materials related to Wallace's research on Native American and Indigenous topics can also be throughout Series I. Correspondence (several of Wallace's correspondents were anthropologists, historians, Native individuals, and other interested parties), Series III. Notecards, Series IV. Works by Wallace, Series V. Works by Others, Series VI. Consulting and Committee Work, Series VIII. ...